Structural optimization of TiO2 supported IrO2 catalyst for proton exchange membrane water electrolysis - Hoffmeister, Darius; Finger, Selina; Pokhrel, Ramesh; Körner, Andreas; Fritsch, Birk; Thiele, Simon; Hutzler, Andreas; van Pham, Chuyen (Chemical Engineering Journal, 2025)
Reducing the iridium loading in proton exchange membrane water electrolysis (PEMWE) is essential, and catalysts with a low iridium content are one viable approach to reach this goal. This study investigates a series of TiO2 supported IrO2 catalysts with three different TiO2 support-particle sizes (3, 14, and 56 m2 g−1) and three different iridium oxide contents (30, 50, and 70 wt%). We demonstrate that, for optimal iridium utilization, the nominal IrO2 shell thickness should be maximized, which is readily achieved by employing low-surface area supports. Following this strategy, a TiO2@IrO2 catalyst with 50 wt% IrO2 is designed, whose single-cell performance exceeds a commercial reference catalyst (88 wt% IrO2) by 43 mV at 2 A cm−2 at a low iridium loading of 0.1 mgIr cm−2. Furthermore, we find a strong correlation between powder conductivity measurements and single-cell high frequency resistance, underlining the importance of catalyst conductivity.
CRIS-Team Scopus Importer:2025-06-13